2022
DOI: 10.1039/d2nr00784c
|View full text |Cite
|
Sign up to set email alerts
|

Pyrenecarboxaldehyde encapsulated porous TiO2 nanoreactors for monitoring cellular GSH levels

Abstract: Recently, ternary electrochemiluminescence (ECL) system has become a research hot due to its great contribution for improving the ECL efficiency by promoting the generation of intermediates. However, it is still...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The ECL and CV results indicated that the TiO 2 acted as the co-reactant accelerator could promote the reduction of S 2 O 8 2– and thus produce more SO 4 •– . The electrons of TiO 2 migrated from the valence band (VB) to the conduction band (CB) during the electrochemical process, in which S 2 O 8 2– can gain electrons to speed up the production of SO 4 •– . When TiO 2 and Ag NPs were sequentially modified on the GCE surface, the ECL intensity for Ag NPs/TiO 2 /GCE was about 4708 au (Figure A, curve c), and the reduction peak current of Ag NPs/TiO 2 /GCE was also increased (Figure B, curve c).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ECL and CV results indicated that the TiO 2 acted as the co-reactant accelerator could promote the reduction of S 2 O 8 2– and thus produce more SO 4 •– . The electrons of TiO 2 migrated from the valence band (VB) to the conduction band (CB) during the electrochemical process, in which S 2 O 8 2– can gain electrons to speed up the production of SO 4 •– . When TiO 2 and Ag NPs were sequentially modified on the GCE surface, the ECL intensity for Ag NPs/TiO 2 /GCE was about 4708 au (Figure A, curve c), and the reduction peak current of Ag NPs/TiO 2 /GCE was also increased (Figure B, curve c).…”
Section: Resultsmentioning
confidence: 99%
“…•− . 33 When TiO 2 and Ag NPs were sequentially modified on the GCE surface, the ECL intensity for Ag NPs/TiO 2 /GCE was about 4708 au (Figure 4A, curve c), and the reduction peak current of Ag NPs/TiO 2 /GCE was also increased (Figure 4B, curve c). Following that, the ECL emitter H 4 TCBPE-TiO 2 nanospheres were modified on the GCE surface, the ECL intensity was 15184 au (Figure 4A, curve d) and the reduction peak located at −0.74 V was evidently more positive than that of bare GCE (Figure 4B, curve d).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Titanium dioxide (TiO 2 ) has become an emerging material in recent years in the biosensing [22] , [23] , [24] , [25] . It was reported that TiO 2 could catalyze the oxidation of H 2 O 2 and aggregate ROS, such as O 2 –• and •OH owing to the band gap dependent catalytic performance of TiO 2 , which contributes significantly to the ECL emission of luminol [26] .…”
Section: Introductionmentioning
confidence: 99%